2018
DOI: 10.1111/anec.12565
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐short heart rate variability recording reliability: The effect of controlled paced breathing

Abstract: Our results indicate that proper ultra-short-term recording method can provide a quick and reliable source of cardiac autonomic nervous system assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
(56 reference statements)
3
23
0
Order By: Relevance
“…Features were extracted within 180 R-R windows with 60 R-R of overlap. Notably, it has been recently demonstrated that the analysis of ultra-short-term recordings provide a reliable source of cardiac autonomic nervous system assessment [ 31 , 32 ]. To reduce inter-individual variability, the whole RR was normalized with zero mean and a standard deviation of one before computing the features.…”
Section: Methodsmentioning
confidence: 99%
“…Features were extracted within 180 R-R windows with 60 R-R of overlap. Notably, it has been recently demonstrated that the analysis of ultra-short-term recordings provide a reliable source of cardiac autonomic nervous system assessment [ 31 , 32 ]. To reduce inter-individual variability, the whole RR was normalized with zero mean and a standard deviation of one before computing the features.…”
Section: Methodsmentioning
confidence: 99%
“…Ultra-short-term HRV refers to an extremely short time segment of RRI record from consecutive heart rate beats less than 1 min, while short-term time segment of RRI record refers to an HRV measure lasting 2-5 min duration. An ultra-short-term HRV record provides time efficiency of data collection in sports training [12,13], psychological measure [14,15], and clinical proposal [16]. Previous studies suggested that a 1 min ultra-short-term HRV record can be used as a surrogate to a traditional 5 min short-term HRV record [12,13,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…HRV is a physiological marker of cardiac autonomic responses that can be detected by recording heartbeat intervals over time. Assessment of daily HRV can provide useful information for understanding cardiac health with regards to labor force workload [ 7 ], mental conditions [ 8 , 9 ], and fitness status [ 10 , 11 ]. In general, the conventional methodology involves recording a 5-minute short-term HRV measurement, followed by a 5-minute stabilization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%